چه‌مكی هاوته‌ریبی له‌ ڕه‌خنه‌ی ئه‌ده‌بیدا (تێڕوانینێكی تیۆری) - محه‌مه‌د, پ.د. دڵشاد عه‌لی; ڕۆسته‌م, م.ی. ئاری عوسمان (Sulaimani Journal for Humanities, 2023)
Parallelism is considered as one of the most significant literary device which distinguishes a poetic manuscript with other literary genres. From this scope Jacobson (1898- 1982) confirmed that in the contemporary criticism parallelism is the essential features pottery. He also assumed that the structure of the poetic manuscript is a constant parallel construction. From this perspective, the study aims to explore the key meaning of the term parallelism and search for its broad definitions. Consequently, it has a significant role to analysis the poetic discourse due to its potential in associating the elements of the poetic manuscript. Hence, the study has classified the conceptual of parallelism into two categories. First, the issues related to this terminology have been discussed. Secondly, the emergence and development of this concept in Western, Arabic and Kurdish literary criticism has been discussed. In the conclusion, outcomes of the study has been presented.